A Synthetic Literature Review and Prognosis of Corporate E-Reputation - Khan, Salman; Digout, Jacques (Indian Journal of Computer Science, 2017)
A synthetic critique of the literature on corporate reputation management and measurement, this paper employs an 'explaining', and 'predicting' approach from a post-modernist stance. The examination covers established definitions, and frameworks, by taking into account the utility in an online environment. The revisit explores central scholarly standpoints and demonstrates a gradual shift from traditional to a digital era of communication. Despite the growing importance of corporate e-reputation, the theory remains hazy and significantly incomplete. The authors also present a feasibility overview of adopting available academic knowledge and tools for reputation management purposes. By establishing a reflexive relationship between reputation and technological advances, this study rhetorically states the prognosis of the subject. Key points of the discussion are conferred in a logical succession. Results petition further conceptual evolution, empirical investigation, and adoption of management and measurement methods for increased practical usage.